BANK SAMPAH: UPAYA PEMBERDAYAAN MASYARAKAT DAN PENANGANAN LINGKUNGAN - Munawir, Munawir (BBM (Buletin Bisnis & Manajemen), 2015)
AbstractThere are regulations of solid waste and kind of solid waste in their households. The people to be responsible with their own solid waste by separating organic and non organic solid waste in their households. Organic solid waste will be processed to become compost as organic fertilizer for all plants. Non organic solid waste will be reuse and recycle to become usefull things or sell them to trash collector. Take in hand by progresif, simultaneous and integrated of organic solid waste and non organic solid waste is reduse big volume of solid waste. One of method in handling non organic solid waste is trash bank.This research about trash, trash bank in Indonesia and the sample of Nirwana Trash Bank located in RW 07, Pedurenan Village, Karang Tengah, Tangerang City. Nirwana Trash Bank has been operating more than two years (since 12 th October 2012), number of member 80 person or only 22,15% of 361 households in RW 07, with 9 personil manajement (8 female, 1 male). Â Keywords: regulations, integrated, reduse, reuse, recycle, trash bank.